Tata Kelola Kolaboratif pada Penetrasi Jaringan Fixed Broadband di Indonesia - Danastry, Aldhira Gusmiara; Kurniawan, Teguh (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
This study aims to explain collaborative governance on fixed broadband network penetration in Indonesia. The case study is used to analyze the application of collaborative governance and the factors that influence the application of collaborative governance to the penetration of fixed broadband networks in Indonesia. This study uses a post-positivism research paradigm with qualitative methods. The government to increase the penetration of fixed broadband networks in Indonesia has implemented a collaborative governance process, as indicated by the implementation of 5 aspects of collaborative efforts (Anshell & Gash, 2008). In the collaboration process, there is a face-to-face dialogue between stakeholders, namely the central government, local governments, BUMN and the community. Build trust between actors because of the relationship and consolidation that occurs. The Distributive Accountability/ Responsibility Factor is applied with a firm division of authorities, duties, and functions among stakeholders in order to achieve the goals of collaboration.